2015
DOI: 10.1590/1516-635x1703347-354
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance, Organ Weights and Some Blood Parameters of Replacement Laying Pullets Fed with Increasing Levels of Wheat Bran

Abstract: This study was conducted to determine the growth performance, organ weights, and selected blood parameters of replacement laying pullets (development phase) fed increasing levels of wheat bran (WB). A total of 240 70-d-old White Leghorn pullets (Hybrid L 33 ) were evaluated for seven weeks. Birds were assigned to three dietary treatments according to a completely randomized design. Treatments consisted of diets containing 100 (T1), 150 (T2), or 200 g/kg (T3) of WB in partial replacement of corn, with 10 replic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 34 publications
0
14
0
2
Order By: Relevance
“…In addition, Walugembe et al (2014) emphasize that the efficiency of fiber utilization in birds is related to intestinal transit time, which changes by poultry species. However, Martínez et al (2015) shows that when unsaturated lipids are added to bird diets rich in fiber, they counteract the negative effect of these structural carbohydrates in the digestive system, because they may reduce the rate of intestinal transit. Aguilar et al (2011), Martínez et al (2015) and Kanakri et al (2017) when including high concentrations of polyunsaturated fat in the bird diets reported similar results.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Walugembe et al (2014) emphasize that the efficiency of fiber utilization in birds is related to intestinal transit time, which changes by poultry species. However, Martínez et al (2015) shows that when unsaturated lipids are added to bird diets rich in fiber, they counteract the negative effect of these structural carbohydrates in the digestive system, because they may reduce the rate of intestinal transit. Aguilar et al (2011), Martínez et al (2015) and Kanakri et al (2017) when including high concentrations of polyunsaturated fat in the bird diets reported similar results.…”
Section: Resultsmentioning
confidence: 99%
“…This work was executed to study the effect of supplementing three multienzyme levels (0, 0.1, and 0.2%) with two types of diet (SD vs. LDD) on immune response, blood hematology and biochemistry, antioxidant status, and organ histology of broilers during 1-38 days of age. The trend in using LDD in feeding broiler chicks has been recently discussed and may be a possible approach to decrease growth pressure on the skeletal system of birds, and reduce feed cost and environmental pollution (23,24,58). Data showed that inclusion of wheat bran in broiler diets at 10% induced a significant growth depression in BWG and FCR only during the early growth period, reaching 6.61 and 6.74%, respectively, which persisted in only BWG during the whole period, reaching 5.6%.…”
Section: Discussionmentioning
confidence: 99%
“…However, T2 depressed the carcass relative weight (Table 3). It found a relationship betweenthe high concentration of secondary metabolites and a decrease of BW and carcass yield, because these phytochemicals apparently develop anti-nutritional factors, which decrease digestion and absorption of nutrients and inflame the small intestine (Woyengo et al, 2011;Martínez et al, 2015). Table 4 shows that the thymus relative weight increased in T2, this is determined by the activation of the immune system, which could increase the production of T cells by jointly destroying the macrophages (Smith & Hunt, 2004;Chen et al, 2013).…”
Section: Effects Of Dietary Supplementation With Red Algae Powder (Chmentioning
confidence: 99%